A caracterização da crônica publicada em jornal - Gabriel Junior, Milton (2015)
This thesis is based on the principle of the Linguistics Textual - Discursive and complemented with the foundations of Critical Discourse Analysis with socio- cognitive aspect, and the New Rhetoric bases for the study of gender as social action, by the American shed. This thesis also reports a research that its main objective is to contribute to studies of Brazilian chronic and there are two objectives: 1. to ascertain the extent to which the opinion columns published in the columns of newspapers Folha de S. Paulo and O Estado S. Paulo can be characterized as textual genre - discursive. It is appropriate to the selected theme since there are several materials, prepared by journalists in the area of media that deal with gender and the treatment have a stated perspective, does not focus on the textual - discursive characterization of newspaper articles published in space called column. This thesis assumes that all social change produces a change in discourse and vice versa. The investigation involved the following instruments: 1. Theoretical and analytical procedure, from contexts, textual sequences and scale of the sequences in a more hierarchical sequence. 2. Selecting the analysis of material were selected texts from 1890 to the present day, published in the newspaper O Estado de S. Paulo and Folha de S. Paulo. 3. The choice of a random date, 08 January in each decade from 30 presenting Brazilian social changes that took place in different historical moments. 4. To demonstrate the non-publication of chronic for some years due to political issues in the various regimes that have made a very tight controls on certain publications and the failure to publish the selected date due to non- newspaper circulation by labor reasons. The results indicate that in space column are published the text - genres chronic, subdivided into news chronic and chronic every day, and article